Penyelenggaraan Angkutan Orang dengan Kendaraan Umum di Surabaya - Wahjoeono, Dipo; Prawesthi, Wahyu (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
One of the efforts made to reduce traffic density in Surabaya is by maximizing both mass and individual public transportation system using available modes such as city buses, paratransit minibuses, taxis and multipurpose transport vehicle. Therefore, it is interesting to assess human transport problems suing public transportation system in Surabaya from jurisdiction point of view in the form of library study involving legislation, references and legal documents related to the problems. In this situation, the enactment of Law No. 22 year 2009 indicates that the implementation of human transport with public vehicles including paratransit minibuses cannot be held by individual, yet, it should be conducted by organization with legal status such as Koperasi or firms.